Tracing the Roots of the Arabic Language: A Systematic Literature Review on Its Historical Development and Linguistic Dynamics - Jannah, Ihda Auliya Ainul; Saputra, Joniska Wawan; Latipah, Ucu; Hijriyah, Umi; Sumanto, Yusika; Basyori, Ahmad (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
This study aims to trace the historical roots and developmental dynamics of the Arabic language through a systematic literature review approach. The method involves collecting and analyzing data from a wide range of classical and contemporary sources, which are thematically categorized into three developmental phases: pre-classical, classical, and modern. The findings reveal that the evolution of Arabic has been shaped by multiple factors, including political expansion, cultural transmission, educational developments, and the central role of religion, particularly within the context of Islam. Moreover, the Arabic language demonstrates a remarkable capacity to adapt to modern challenges while retaining its linguistic identity. These insights contribute to a deeper understanding of Arabic’s historical trajectory and the external forces influencing its transformation, offering valuable implications for Arabic linguistic studies and the preservation of Semitic language heritage.